Does Economic Complexity Promote Inclusive Green Growth - Emmanuel Y. Gbolonyo; Isaac K. Ofori; Nathanael Ojong (ZBW - Leibniz Information Centre for Economics, 2024)
Despite the growing scholarly attention concerning the effect of economic complexity (ECI) on inclusive growth and the environment, there remain some pertinent gaps in the literature. First, previous studies have not explored the effect of ECI on inclusive green growth (IGG). Second, prior contributions have not assessed the role of energy consumption (disaggregated into renewable and non-renewable) in the relationship between ECI and IGG. This study addresses these gaps by using macro data for 22 selected African countries. Robust evidence based on the dynamic system GMM and the Driscoll-Kraay standard errors estimators reveal that economic complexity promotes IGG. Additionally, the contingency analysis reveals that non-renewable energy diminishes the IGG-enhancing effect of ECI, whereas renewable energy amplifies it. Finally, when we decompose IGG into environmental and socioeconomic sustainability, we find that the ECI-energy consumption interaction has a greater effect on the latter rather than the former. We conclude that investments for boosting Africa's productive knowledge and renewable energy capacities are crucial for IGG.
Keywords: O44; O55; Q01; Q43; Q56; 330; Africa; Economic Complexity; Renewable Energy Consumption; Inclusive Green Growth